2022
DOI: 10.1152/ajplung.00233.2022
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette vapor exposure in utero causes long-term pulmonary effects in offspring

Abstract: The in utero environment is sensitive to toxicant exposure, altering the health and growth of the fetus, and thus sensitive to contaminant exposure. Though recent clinical data have the use of e-cigarettes does no further harm to birth outcomes than a nicotine patch, this does not account for the effects of vaping during pregnancy on the long-term health of offspring. Pregnant mice were exposed to: (a) e-cigarette vapor with nicotine (PV + Nic; 2% Nic in 50:50 propylene glycol: vegetable glycerin), (b) e-cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A study with rats suggested that prenatal exposure to e-cigarette vapor was associated with lower birth weight, as well as a decrease in blood flow to the maternal uterine and fetal umbilical circulation. Even e-cigarettes that are nicotine free contain aerosols and flavorings that could potentially lead to developmental toxic effects, as well as compromised lung development and pulmonary function in the fetus . For example, flavoring chemicals in e-cigarettes have been shown to impact hippocampal development with microglia activation and altered expression of neurotrophins in mice .…”
Section: Introductionmentioning
confidence: 99%
“…A study with rats suggested that prenatal exposure to e-cigarette vapor was associated with lower birth weight, as well as a decrease in blood flow to the maternal uterine and fetal umbilical circulation. Even e-cigarettes that are nicotine free contain aerosols and flavorings that could potentially lead to developmental toxic effects, as well as compromised lung development and pulmonary function in the fetus . For example, flavoring chemicals in e-cigarettes have been shown to impact hippocampal development with microglia activation and altered expression of neurotrophins in mice .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the developmental origin of health and disease, in utero exposure to environmental pollutants can alter the trajectory of heath by increasing the susceptibility to chronic diseases later in life [ 14 , 15 , 16 , 17 , 18 , 82 ]. It is well-documented that the lungs are sensitive to ‘fetal programming’, as epidemiological and experimental evidence shows that in utero exposure to cigarette smoke, second-hand smoke, and ENDS aerosols can lead to adverse pulmonary responses in the offspring, including increased risk of developing asthma [ 11 , 12 , 13 , 22 , 23 , 82 , 83 ]. Asthma is a chronic lung disease affecting 339 million individuals worldwide, including children [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, we found that molecular signatures induced by in utero mint-flavored JUUL aerosols on the lungs of male mouse offspring persisted until 11 weeks of age and consisted of 16 genes, which were mainly down-regulated [ 23 ]. Further, it was recently shown that in utero exposures to unflavored e-cig aerosols, with or without nicotine, affect lung structure and function in adult 5-month-old offspring [ 83 ]. Together, these results clearly demonstrate that long-term pulmonary sequelae are associated with a single in utero e-cig aerosol exposure in mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BallbèM et al [10] detected low but nonnegligible concentrations of e-smoke-associated analytes in cord blood and breast milk of nonuser pregnant women exposed to e-cigarettes. Aslaner DM et al [11] also demonstrated that the inhalation of second-hand e-cigarette smoke by pregnant women can have long-term effects on the lungs of offspring. At the same time, because the nicotine content in e-cigarette smoke is equivalent to, or even higher than, that in the combustible smoke [12] , the drug addiction damage caused by e-cigarette smoke to the human body cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%